Influence of PVDF/Pebax TFC Casting Temperature towards CO2/N2 Gas Separation - Abdul Wahab, Mohammad; Sunarti, Abd Rahman (Informatics Publishing Limited, 2017)
Objectives: A Thin Film Composite (TFC) membranes has been successfully synthesized via introducing casting temperature adjustment to counter the permeability-selectivity conflict. Methods: 15 wt% Polyvinylidene Fluoride (PVDF) was diluted in 85 wt% N-Methyl-2-Pyrrolidone (NMP) and cast on a glass plate at 40°C-80°C. To form the TFC, 3 wt% of Polyether block amides (Pebax 1657) was used as a coating layer on top of the PVDF substrate. Findings: The surface roughness of the samples cast at 60°C was measured to be 102.6 nm while the other is less than 100 nm and the CO2 and N2 flux was measured to be 749 and 13 barrer respectively with CO2 /N2 selectivity of 58.54. Application: The result has been plot on Robeson 1991 and it fall beyond the upper boundaries, indicate that the future of coating material and casting techniques can be further explored to maximize the limit of material capabilities.